Community studies: Fort McMurray, Anzac, Fort MacKay ... - Loberg, C.; Van Dyke, E. W. (University of Alberta Library, 1978)
The present study is descriptive in nature; the focal point is to develop insights into social and human problems in the Athabasca Oil Sands region. Of three communities studied, Fort McMurray received the most comprehensive treatment, partly because it is more accessible to data collection than Anzac and Fort MacKay, and partly because, as the centre of the resource development in the area, it exemplifies the complexity and range of issues involved. The research techniques included participant observation and both directed and non-directed in-depth interviews. members of the study team lived in the area for over six months; during this time they interviewed 43 persons to gain general knowledge of various aspects of the lives of these persons from the time they first heard of Fort McMurray to the present. The respondents were diversified as much as possible to length of residence in the area, age, sex, occupation, residential location, etc. To synthesize results of this research, the information gathered has ...